The Passing of the Frontier: A Chronicle of the Old West - Hough, Emerson, 1857-1923 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Passing of the Frontier: A Chronicle of the Old West" by Emerson Hough is a historical account written in the early 20th century. This work explores the essence and significance of the American frontier, highlighting its role in shaping American identity and culture. Through various lenses$1 (Bincluding the lives of frontiersmen, the impact of westward expansion, and the rugged landscapes that defined the era$1 (BHough paints a vivid picture of the Old West. At the start of the book, Hough reflects on the deeply ingrained meaning of the frontier in American history, tying it to themes of adventure, individualism, and self-reliance. He delves into the evolution of the frontier, likening its allure to that of folklore, while framing it as a space characterized by both opportunity and hardship. The opening portions also outline the connections to early exploration, referencing figures like Lewis and Clark, and set the stage for discussing the subsequent waves of settlers and pioneers, drawing attention to the transformation of the land and the people$1 (Bespecially the cattle ranchers and miners$1 (Bwho shaped this critical period in American history. (This is an automatically generated summary.)s
Chronicles of America series; v. 26
Release date is 2002-01-01
The James J. Kelly Library of St. Gregory's University, Alev Akman, and David Widger
Keywords: West (U.S.) -- History; Frontier and pioneer life -- West (U.S.)